Effect of COVID 19 lockdown on a group of young Egyptian athletes - Nassar, M.; Allam, M.; Shata, M. (2020)
OBJECTIVE: The current study was designed to highlight the physical and psychological health hazards that young Egyptian athletes faced during the COVID-19 lockdown. SETTING: Private sporting club in Cairo. DESIGN: Cross sectional study. PARTICIPANTS: This study included 37 young Egyptian male soccer players whose ages ranged between 9 and 11 years. INTERVENTIONS: Each athlete was subjected to detailed history taking and their anthropometric measurements were taken, mainly weight and height with calculation of their body mass index (BMI). Two questionnaires were filled by each of the enrolled athlete covering their sleep habits and their quality of life (QoL). Finally, the mothers were asked to fill in a questionnaire concerned with depression, anxiety and stress. RESULTS: More than 50% of the enrolled athletes gained weight during the lockdown. Significantly more young athletes who gained weight reported no compliance to the assigned home exercises and more sleeping hours. The mothers' depression score correlated negatively and their anxiety score correlated positively with the increased BMI of the athletes. The athletes mean QoL Score worsened significantly from March to July 2020. Additionally, a significant negative correlation was found between the increased BMI and the change of QoL. CONCLUSION: The recent pandemic lockdown had both physical and psychological effects on Egyptian young athletes. The increased BMI was significantly reported among those who didn't do home exercises and had a negative correlation with their QoL change throughout the lockdown. Additionally, the mothers' depression and anxiety had a possible reflection on their youngsters' weight gain.